Akkermansia muciniphila Promotes Bone Development and Improves Eggshell Quality during the Sexual Maturity Period of Laying Hens by Increasing Osteogenesis - Zhengtian Lyu; Yuying Zhang; Gaoxiang Yuan; Fengwenhui Zhang; Yongfei Hu; Dan Liu (Agriculture, 2024)
Adequate bone development is imperative for maintaining the health and productivity of laying hens. Probiotics play a pivotal role in promoting bone formation and preventing osteoporosis. This study aimed to explore the effect of Akkermansia muciniphila (Akk) on the bone development and eggshell quality of laying hens during the rearing period. A total of 300 1-day-old Jingfen NO. 6 commercial pullets were categorized into two groups, one of which was fed a conventional diet for 20 weeks (Control group), the other group was fed a conventional diet with lyophilized Akk powder for 20 weeks (Akk group). During the first two weeks, pullets in the Akk group received live Akk inoculation, while birds in the Control group received normal saline administration. Micro-computed tomography analysis was employed to evaluate three bone microarchitectures: cortical bone (Cb), trabecular bone (Tb), and medullary bone (Mb). Our findings revealed that supplementation with Akk powder increased the thickness and bone mineral content of Cb and Tb, while simultaneously reducing the volume and bone surface area of Mb. The increased activity of alkaline phosphatase, a marker of osteogenesis, and the decreased activity of tartrate-resistant acid phosphatase, a marker of osteoclastic activity, were observed in the Akk group. Dietary supplementation of Akk powder improved the immune microenvironment in the bone marrow by increasing osteogenic-related CD8+ T cells and decreasing osteoclastogenesis-related CD4+ T cells. Additionally, Akk powder supplementation significantly enriched the Lactobacillaceae family in cecum. The enhancement of bone development by Akk contributed to increased eggshell strength and thickness. These findings demonstrate the osteomodulatory effects of Akk in laying hens and the connections between bone physiology and eggshell quality, highlighting the importance of gut–bone communications in laying hens.